2017
DOI: 10.1158/2326-6066.cir-16-0073
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid STAT3 Promotes Lung Tumorigenesis by Transforming Tumor Immunosurveillance into Tumor-Promoting Inflammation

Abstract: One of the most fundamental and challenging questions in the cancer field is how immunity in cancer patients is transformed from tumor immunosurveillance to tumor-promoting inflammation. Here, we identify the transcription factor STAT3 as the culprit responsible for this pathogenic event in lung cancer development. We found that antitumor type 1 CD4+ T helper (Th1) cells and CD8+ T cells were directly counter-balanced in lung cancer development with tumor-promoting myeloid-derived suppressor cells (MDSCs) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 48 publications
0
66
0
Order By: Relevance
“…The EGFR signaling pathway plays a role in recruiting Tregs and macrophages to the TME, which can explain the decrease of both cell types upon EGFR inhibition. Nevertheless, the activation of STAT3 in MDSCs may transform tumor immunosurveillance into tumor‐promoting inflammation through the induction of Tregs, inhibition of DCs, and the polarization of macrophages toward the M2 phenotype . In addition, we found that IL‐10, which is known to be an activator of the STAT3 pathway, was also elevated by long‐term EGFR inhibition.…”
Section: Discussionmentioning
confidence: 75%
“…The EGFR signaling pathway plays a role in recruiting Tregs and macrophages to the TME, which can explain the decrease of both cell types upon EGFR inhibition. Nevertheless, the activation of STAT3 in MDSCs may transform tumor immunosurveillance into tumor‐promoting inflammation through the induction of Tregs, inhibition of DCs, and the polarization of macrophages toward the M2 phenotype . In addition, we found that IL‐10, which is known to be an activator of the STAT3 pathway, was also elevated by long‐term EGFR inhibition.…”
Section: Discussionmentioning
confidence: 75%
“…The immune‐suppressive action of IL‐6 could also occur at the level of myeloid cells. IL‐6/STAT3 signaling directs myeloid cells to produce immune‐suppressive molecules such as VEGF and arginase that help tumor cells escape from immune surveillance . IL‐6 conversely inhibits the expression of MHC‐II, CD80/86, and IL‐12 in DC or re‐programs the differentiation into IL‐10‐producing regulatory DC .…”
Section: Pleiotropic Immunomodulatory Effects Of Il‐6 Signaling In Mymentioning
confidence: 99%
“…STAT3 is a member of the STAT protein family, which is phosphorylated by the receptor-associated kinases in response to cytokines and growth factors, and then forms heterodimers that translocate to the cell nucleus where they function as transcription activators. It has been widely reported that STAT3 play significant roles in the cell growth, EMT, oncogenic transformation, tumorigenesis, progression and immune evasion of lung cancer [46][47][48]. The E2F1 transcription factor is realized as a regulator of the cell cycle as well as a potent mediator of DNA damage-induced apoptosis and the checkpoint response.…”
Section: Discussionmentioning
confidence: 99%